The war an intimate history, 1941-1945 - Ward, Geoffrey C. (A.A. Knopf, 2007)
As companion to his PBS series airing in September 2007, "The War" focuses on the citizens of four towns--Luverne, Minnesota; Sacramento, California; Waterbury, Connecticut; Mobile, Alabama, following more than forty people from 1941 to 1945. Maps and hundreds of photographs enrich this compelling, unflinching narrative.